Reasons for the Frequent Procedures of Bariatric Surgery - Noaman, Aqeel Abbas; Jassim, Nabaa Ali; Fahad, Morooj Ali (International Journal of Psychosocial Rehabilitation, 2020)
Background: Obesity is clinically defined as an abnormal increase in weight, which can be determined by the use of body mass index (BMI) and it is necessary to adopt this indicator regularly because obesity is considered a health condition of concern globally due to its increased prevalence day by day and its association with many Life-threatening health risks.Objectives: The study aims to identify demographic factors that increase the chances of bariatric surgery and the type of surgery most commonly used and the most common reason.Patients and methods: An analytical cross-sectional study was conducted for non-probability random sample of obese patients who accepted obesity surgery in Baghdad and Diyala city, all of whom underwent these operations after being informed by the surgeon they had obesity and not overweight. A simple questionnaire was distributed to patients after initial approval from them to participate in the research sample, the questionnaire contained general demographic information about the patient in addition to the inclusion of a set of reasons why the patient underwent bariatric surgery. The evidence was introduced into the program of statistical packages of social sciences (SPSS), version (21) to summarize the results of the study. A chi-square test was used for statistical testing and a level below (0.05) for statistical significance.Results: The current study found that the mean age of patients who underwent a type of bariatric surgery was 37.22 years, most of them were women (63.3%) and employees( 60%) respectively. More than half (56.7%) were had university education. The results also showed that 70 percent of respondents said they had Laparoscopic Sleeve Gastrectomy and 50 of them the most common reason for performing bariatric surgery was to improve their external appearance and improve their fitness. Conclusions: Most of the patients who underwent Laparoscopic Sleeve Gastrectomy to treat obesity were found to be significantly, and the most common reason for performing these surgeries was to improve their external appearance and improve their fitness.